Volver la atención a los exámenes de lengua, una paradoja en las universidades colombianas - Restrepo Rodas, Jonathan (Colombian Applied Linguistics Journal, 2024)
Since 2020, in Colombia it is required that students of bachelor's degrees in foreign languages obtain a level of sufficiency (C1) that confers the validity of the knowledge of the language and culture as a degree requirement (MEN, 2017). Language policy posits that language tests measure students’ language skills as well as (inter)cultural notions and attitudes. However, from a socio-cognitive lens, the conception of the tests does not say much about the cognitive and social processes that become crucial for taking the exams. Therefore, it seems relevant to review the ontology of institutional language exams and to identify what aspect gives coherence and validity to the obtention of such tests as a degree requirement. To achieve this, a phenomenological description is proposed. The hypothesis of the manuscript says as follows: language tests, instead of measuring the linguistic and (inter)cultural skills of students, surround above all, their social and cognitive systems, especially morality. As a result, it could be postulated that the conception of standardized tests as a degree requirement requires profound and rapid changes.